1996
DOI: 10.1073/pnas.93.1.362
|View full text |Cite
|
Sign up to set email alerts
|

Efflux pump of the proton antiporter family confers low-level fluoroquinolone resistance in Mycobacterium smegmatis.

Abstract: Due to the resurgence of tuberculosis and the emergence of multidrug-resistant strains, fluoroquinolones (FQ) are being used in selected tuberculosis patients, but FQ-resistant strains of Mycobacterium tuberculosis have rapidly begun to appear. The mechanisms involved in FQ resistance need to be elucidated if the effectiveness of this class of antibiotics is to be improved and prolonged. By using the rapid-growing Mycobacterium smegmatis as a model genetic system, a gene was selected that confers low-level FQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 40 publications
3
120
1
1
Order By: Relevance
“…Perhaps more importantly, M. smegmatis has proven to be a more suitable surrogate host than conventional host organisms such as E. coli, B. subtilis, or Streptomyces for investigating the molecular biology of mycobacteria. Isolation of mc 2 155 allowed for the identification of genes involved in isoniazid (68)(69)(70)(71), ethionamide (72,73), isoxyl (74,75) or thioacetazole (75), ethambutol (76)(77)(78), capreomycin (79), streptomycin (80), fuoroquinolone (81), and kanamycin (79) resistance. The ability to transform and express genes in M. smegmatis allowed the discovery of the first auxiliary secA2 secretion system (82), a novel way to study iron metabolism (83), and the analyses of unique carbohydrate antigens (84).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more importantly, M. smegmatis has proven to be a more suitable surrogate host than conventional host organisms such as E. coli, B. subtilis, or Streptomyces for investigating the molecular biology of mycobacteria. Isolation of mc 2 155 allowed for the identification of genes involved in isoniazid (68)(69)(70)(71), ethionamide (72,73), isoxyl (74,75) or thioacetazole (75), ethambutol (76)(77)(78), capreomycin (79), streptomycin (80), fuoroquinolone (81), and kanamycin (79) resistance. The ability to transform and express genes in M. smegmatis allowed the discovery of the first auxiliary secA2 secretion system (82), a novel way to study iron metabolism (83), and the analyses of unique carbohydrate antigens (84).…”
Section: Discussionmentioning
confidence: 99%
“…LfrA confers resistance to hydrophilic quinolones but not to the more hydrophobic quinolones (134). Hybridization analysis showed that LfrA homologs are present in M. tuberculosis and Mycobacterium avium (244).…”
Section: Major Facilitator Superfamilymentioning
confidence: 99%
“…LfrA, an MFS efflux pump that confers resistance to fluoroquinolones, EtBr, acridine, and quaternary ammonium compounds, was the first such pump characterized in mycobacteria (53). More recently, other efflux pumps have been demonstrated to be involved in mycobacterial drug resistance (17).…”
Section: Discussionmentioning
confidence: 99%